Service-oriented dynamic resource configuration optimization scheme in RFID system - Jian-hua LIU; Wei-qin TONG (Tongxin xuebao)
Aiming at the defect that the rate between tag and reader was not match and their resource-constrained problem in the radio frequency identification(RFID)systems,the collaboration communication context was analyzed theoretically.Service-oriented dynamic resource configuration optimization scheme of RFID system was proposed which used the component quality of service(QoS) information of tag and reader to establish closed-loop control framework and developed three control strategies to adjust QoS parameter according to the state and type of its resources.The scheme was analyzed and validated for performance through experiments.The numerical experiments results show that the optimization mechanism make throughput of RFID systems improve,use resources efficiently and reduce the energy consumption and interference of reader-to-reader.